2016
DOI: 10.1615/jenvironpatholtoxicoloncol.2016015463
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Light- or Sonic-Activated Drug Delivery: Photochemical/Sonochemical Internalization

Abstract: Photochemical internalization (PCI) is a technique that uses the photochemical properties of photodynamic therapy (PDT) for the enhanced delivery of endolysosomal-trapped macromolecules into the cell cytoplasm. The released agent can therefore exert its full biological activity, in contrast to being degraded by lysosomal hydrolases. Activation of photosensitizers via ultrasound (US), called sonodynamic therapy (SDT), has been proposed as an alternative to light-activated PDT for the treatment of cancerous tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The results shown in Figure 5B, employing this model, demonstrated that SDT potentiated the cytotoxic effects of BLM to a significant degree. This was the case regardless of the sequence of SDT and BLM application, although SDT before drug was more effective [42,45]. This synergistic effect is postulated to be due to endosomal escape, in a similar manner to that seen for light-based PCI [46,47].…”
Section: Review Hirschberg and Madsenmentioning
confidence: 71%
See 2 more Smart Citations
“…The results shown in Figure 5B, employing this model, demonstrated that SDT potentiated the cytotoxic effects of BLM to a significant degree. This was the case regardless of the sequence of SDT and BLM application, although SDT before drug was more effective [42,45]. This synergistic effect is postulated to be due to endosomal escape, in a similar manner to that seen for light-based PCI [46,47].…”
Section: Review Hirschberg and Madsenmentioning
confidence: 71%
“…The overall damage induced by SDT is closely related to the precise subcellular localization of the sonosensitizer. Figure 3 [42]. Fluorescence microscopy was used to verify the uptake and intracellular localization of AlPcS 2a in the absence or presence of FUS.…”
Section: Endosomal Entrapmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the molecular mechanisms of SDT for GBM treatment through in vitro and in vivo experiments. Many drugs, including 5-ALA [ 44 52 ], fluorescein [ 53 ], rose Bengal [ 54 ], hematoporphyrin mono-methyl ether (HMME) [ 38 , 55 60 ], sino-porphyrin [ 61 63 ], photofrin [ 64 , 65 ], photolon [ 66 , 67 ], protoporphyrin IX (ppIX) [ 52 ], talaporfin sodium [ 52 ], aluminum phthalocyanine disulfonate (AlPcS 2a ) [ 68 , 69 ], and titanium dioxide (TiO 2 ), have been used as sonosensitizers [ 70 , 71 ], which mainly accumulate in the mitochondria (Table 1 ).…”
Section: Killing Mechanisms Of Sdtmentioning
confidence: 99%
“…SDT with US (1.0 MHz, duty cycle of 80%, 1.8 W/cm 2 , 1 min) exerted the greatest inhibitory effects on the viability of U87MGde 2–7 cells, with the highest generation of ROS. To compare the efficacy of SDT and PDT in combination with chemotherapy, Madsen et al [ 68 ] investigated ultrasonic and photic activation of AlPcS 2a together with the anticancer agent bleomycin (BLM) to treat F98 cells. The author aimed to compare the effects of photochemical internalization (PCI) and sonochemical internalization (SCI) on tumor cells.…”
Section: Sdt-based Combination Treatment Of Gbmmentioning
confidence: 99%